Sources and Use of Sexual and Reproductive Health Information Among Deaf People in Ghana - Wisdom Kwadwo Mprah (Indonesian Journal of Disability Studies, 2014)
While information is critical for making informed decisions on SRH issues, the deaf community in Ghana has limited access due to social, economic, and institutional barriers. The purpose of this article is to describe the sources and use of Sexual and Reproductive Health (SRH) information among deaf people in Ghana. Data for this article were derived from a SRH needs assessment project with deaf people in Ghana. The study involved 179 participants, consisting of 178 deaf participants” 26 focus group participants, 152 survey respondents” and one hearing person served as a key informant. Findings from both the focus groups and survey revealed that deaf people in Ghana obtained SRH information from a wide range of sources: school teachers, family members, health professionals, friends, the media, and SRH organizations and centers. The study findings also indicated that although health professionals are the official source of information on SRH issues in Ghana, they were not the most utilized and preferred source for the deaf community due to communication barriers. These findings are consistent with other studies and suggest that any SRH program aimed at improving access to information to the deaf population should endeavor to eliminate communication barriers.